HISTORY TOMB OF DATUK ABDURRAHIM BIN ABU BAKAR IN LATENG, BANYUWANGI, EAST JAVA AS A HISTORY LEARNING SOURCE IN BANYUWANGI 1 STATE HIGH SCHOOL - Asy'ari, Faruq Hasan; Ediyono, Suryo (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2022)
Datuk Abdurrahim Bin Abu Bakar is known as a preacher of Islam, namely spreading Islam in various areas, especially Banyuwangi. Every day, the tomb of Datuk Abdurrahim Bin Abu Bakar is never empty of pilgrims who come from various regions with different goals and motivations. The tomb, which is located not far from the city center of Banyuwangi, is very sacred to the people of Banyuwangi. This is very unique, because usually the graves that are sacred to the community are located in forests, hills, and beaches, which are far from residential areas. The further uniqueness of the name of the tomb itself. At the beginning of the name there is the word "datuk", the word comes from the Malay culture which is used to address an old man. If you look at the culture in Banyuwangi, East Java, to call an old man by using the word "mbah". In this research, it can be collected using the historical method with stages; (1) heuristics, (2) source criticism, (3) interpretation, (4) historiography. The purpose of this research is to; (1) Knowing the history of the Tomb of Datuk Abdurrahim Bin Abu Bakar, (2) Knowing the potential of the Tomb of Datuk Abdurrahim Bin Abu Bakar Bin Abdurrahim Bauzir as a source of learning history in high school and the values of character education in compulsory history learning for class X according to the 2013 curriculum, such as; tolerance, religious, honesty, helpful help, hard work, and discipline. It is hoped that further researchers can complement the research results that have been written by current researchers  Keywords: Tombs, Character values, History Learning Resources